RADIONUCLIDE CONCENTRATIONS AND IMPACT ASSESSMENT OF THE JOS TIN MINING SOIL RESIDUES - Odusote, O. O.; Alausa, S. K.; Gyang, B. N. (The Nucleus, 2014)
This study was performed to measure the radionuclides in the tin mining soil mounds from the Jos Plateau, Nigeria and to evaluate the impact of radiation on the environment where the soils are used as building materials. Gamma spectrometry was employed via a NaI(Tl) detector to determine the activities of the radionuclides 40K, 238U and 232Th in ten (10) samples from points within a distance of 20 km along the mining trail. The results of measurements of natural radionuclide ( 238U, 232Th and 40K) in soil samples show that the concentrations of 238U, 232Th and 40K ranged between 1.51 – 4.98, BDL - 8.64 and 10.3 – 35.2 Bq/kg with mean concentrations of 3.20 1.16, 1.31 2.75 and 25.60 8.89 Bq/kg, respectively. The external hazards ranged between 0.008 – 0.044 with mean value of 0.019 0.009 while the internal hazards ranged between 0.014 – 0.048 with mean value of 0.028 0.009. These hazard values are less than 1. The annual gonadal dose equivalent (AGDE) ranged between 10.28 – 55.87 Svy-1 with mean value of 24.22 12.16 Svy-1 . The radium equivalent activities ranged from 3.07 – 16.23 Bq/kg with a mean value of 7.04 3.53 Bq/kg. The external absorbed dose rate ranged from 5.35– 18.76 Gyh-1 with a mean value of12.95 4.26 Gyh-1 . The internal absorbed dose rate ranged from 10.34 – 35.53 Gyh-1 with an average value of 24.87 8.13 nGyh-1 . The external absorbed dose equivalent rate ranged from 0.007- 0.023 with a mean value of0.016 . The internal absorbed dose equivalent rate ranged from 0.051 – 0.174 with an average value of 0.122 . All the calculated radiological indices fall within the recommended safe limits and world averages. The soil mounds, therefore, do not constitute environmental radiation risks and the soils could be used in construction.